Integrating social protection and child protection services for better outcomes for children in the Middle East and North Africa - Karen Codazzi Pereira; Fernando Araújo (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
This Research Report, developed by the IPC-IG and the UNICEF MENA Regional Office for Middle East and North Africa, presents five case studies that demonstrate how integrated social protection and child protection systems enhance efficiency, especially of the social service workforce, and improve socio-economic and child outcomes: Tunisia, Morocco, Iraq, Egypt, and Brazil.
Keywords: 330; social protection; child protection; social service workforce